2018
DOI: 10.1016/j.jhsa.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of Diagnostic Tools for the Diagnosis of Carpal Tunnel Syndrome

Abstract: Consideration should be given to using alternative diagnostic tests/tools based on the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
(10 reference statements)
1
21
1
1
Order By: Relevance
“…14 Studies are consistent in finding that EDS is not the reference standard test to diagnose CTS and that physical examination findings alone are sufficient to diagnose CTS in patients with classic symptoms. 1520 Furthermore, previous studies demonstrated that for patients with a high probability of CTS based on examination criteria alone, EDS does little to change the probability of diagnosis. 18,21 Wang et al 20 recently demonstrated the relatively poor specificity of nerve conduction studies in the prospective diagnosis of CTS, which means that the routine use of EDS as a confirmatory test to diagnose CTS before a surgical consultation could be considered wasteful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Studies are consistent in finding that EDS is not the reference standard test to diagnose CTS and that physical examination findings alone are sufficient to diagnose CTS in patients with classic symptoms. 1520 Furthermore, previous studies demonstrated that for patients with a high probability of CTS based on examination criteria alone, EDS does little to change the probability of diagnosis. 18,21 Wang et al 20 recently demonstrated the relatively poor specificity of nerve conduction studies in the prospective diagnosis of CTS, which means that the routine use of EDS as a confirmatory test to diagnose CTS before a surgical consultation could be considered wasteful.…”
Section: Discussionmentioning
confidence: 99%
“…1520 Furthermore, previous studies demonstrated that for patients with a high probability of CTS based on examination criteria alone, EDS does little to change the probability of diagnosis. 18,21 Wang et al 20 recently demonstrated the relatively poor specificity of nerve conduction studies in the prospective diagnosis of CTS, which means that the routine use of EDS as a confirmatory test to diagnose CTS before a surgical consultation could be considered wasteful. Although EDS may be helpful in scenarios in which the diagnosis is unclear, using EDS routinely as a confirmatory test has little value in directing treatment recommendations for patients with classic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, CTS is characterized by multiple alterations, both motor and sensory [ 21 ]: nocturnal paraesthesia, numbness, tingling, decreased sensitivity and pain in the territory innervated by the median nerve, decreased grip strength, and atrophy of the thenar eminence [ 22 ]. Recent evidence defines CTS as a complex pain syndrome characterized by the presence of clinical, physical, neurophysiological, and psychological factors involving peripheral and central sensitization processes [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy of the upper limbs due to compression of the median nerve at the level of the carpal tunnel. 1 The diagnosis is usually made through clinical history and physical examination, 2 while electroneuromyography (ENMG) assists in the diagnostic confirmation of doubtful cases and in establishing the severity. 3,4 In 1990, Katz et al 5 popularized hand diagrams, which are schematic drawings in which the patient marks the exact location of the numbness symptoms in the hands.…”
Section: Introductionmentioning
confidence: 99%